Reading a painting: Maxo Vanka’s collage “World War II” - Henry A. Christian; Tine T. Kurent (Dve Domovini, 1997)
The interpretation of symbols on the collage “The Beginnings of World War II” by the American-Croatian painter Maxo Vanka is the story about the escape of Dr. Stetten, Vanka’s father-in-law, from the occupied France via the MS Ile de France, and about the exposal of a nazi agent, Douglas Chandler, by Vanka and his friend, the American-Slovene writer Louis Adamic.